Hearing Thresholds Changes after MRI 1.5T of Head and Neck. (17th June 2019) - Bahaloo, Maryam; Davari, Mohammad Hossein; Sobhan, Mohammad; Mirmohammadi, Seyyed Jalil; Jalalian, Mohammad Taghi; Zare Sakhvidi, Mohammad Javad; Shamsi, Farimah; Mirfendereski, Sam; Mollasadeghi, Abolfazl; Mehrparvar, Amir Houshang
Abstract : Introduction . Exposure to high intensity noise produced by MRI is a cause for concern. This study was conducted to determine the temporary and permanent effects of exposure to noise created by performing MRI on the hearing threshold of the subjects using conventional and extended high frequency audiometry. Methods . This semiexperimental study was performed on 35 patients referred to Shahid Rahnemoun Hospital for head and neck MRI due to different clinical conditions. The hearing threshold of patients was measured before, immediately after, and 24 hours after performing 1.5 Tesla MRI using conventional and extended high frequency audiometry. SPSS version 18 was used to compare the mean hearing thresholds before and after MRI using paired T test and repeated measures analysis. Results . Comparison of auditory thresholds in conventional and extended high frequencies before and immediately after MRI showed a significant shift at 4 KHz (P = 0.008 and P = 0.08 for right and left ears), 6 KHz (P = 0.03 and P = 0.01 for right and left ears), and 14 KHz (P =0.03 and P = 0.31 for right and left ears). However, there was no significant difference between audiometric thresholds before and 24 hours after MRI. Conclusion . Noise due to 1.5 Tesla MRI can only cause transient threshold shift.